Effects of Adding Brown Sugar In Young Coconut Water Post High-Intensity Interval Training on Plasma Osmolarity, Oxygen Saturation, and Pulse Rate - Muhammad Redy Arif Pradana; Gadis Meinar Sari; Bambang Purwanto; Maharani Fatima Gandasari; Rakhmat Nur Hidayat; Slamet Raharjo; Muhammad Muhammad (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study analyzes the effect of adding brown sugar to young coconut water post-High Intensity Interval Training (HIIT) on plasma osmolarity, oxygen saturation, and pulse rate. Utilizing a pre and post-test control group design, the experiment involved 20 male subjects aged 19-22 with a normal body mass index. The participants were divided into three groups: (K1) receiving mineral water, (K2) receiving young coconut water, and (K3) receiving young coconut water with added brown sugar. Each subject underwent a 30-minute ergo cycle HIIT session. Blood samples were collected at three intervals: before exercise, immediately after, and an hour post-rehydration. The results indicated plasma osmolarity levels showed no significant change from Pre-HIIT (0.939) to Post-HIIT (0.780). However, Post-Rehydration, an increase was observed across the three groups (p=0.004). Pulse rate measurements revealed no significant difference from Pre-HIIT (0.788) to Post-HIIT (0.411), but Post-Rehydration, a significant decrease was noted between the groups (p=0.034). Oxygen saturation levels remained consistent Pre-HIIT (0.902), Post-HIIT (0.602), and 1-hour post-HIIT (0.611) within the third group. In conclusion, adding brown sugar to young coconut water post-HIIT resulted in higher plasma osmolarity, did not affect oxygen saturation levels, and contributed to a lower pulse rate.